Pyrene Appended Free‐base, Phosphorus(V) and Gallium(III) Corroles and Their β, β′‐Linked Corrole Dimers: Synthesis, Photophysical and Electrochemical Properties. Issue 6 (1st February 2021) - Sujesh, S.; Basumatary, Biju; Kumar, Amit; Sankar, Jeyaraman
Abstract: Pyrene appended free‐base, phosphorus(V) and gallium (III) corrole conjugates were synthesized and characterized. Efficient β‐β′ dimerization of corroles was achieved by oxidation with p ‐chloranil in moderate yield from their respective metallated corroles. The weak ground state electronic coupling between pyrene and corrole units was established by photophysical and electrochemical investigations. The fluorescence spectral studies showed a red shifted emission maximum for dimer with respect to their monomeric counterpart due to possible π‐conjugation and supported by the density functional theory (DFT). The electrochemical investigation revealed multiple oxidation associated with the corrole and pyrene centers. Abstract : Synthesis, characterization, photophysical and electrochemical analyses of pyrene appended corrole macrocycles (free base, phosphorous(V) and gallium(III)) and their respective β‐β′ dimer molecules are presented.